Comparison of the analgesic effect of ultrasound-guided paravertebral block and ultrasound-guided retrolaminar block in Uniportal video-assisted Thoracoscopic surgery: a prospective, randomized study - Qiang Wang (BMC, 2021)
Abstract Background The optimal modality for postoperative analgesia after uniportal video-assisted thoracoscopic surgery (UVATS) for the treatment of lung cancer has not yet been determined. Both ultrasound-guided paravertebral block (PVB) and retrolaminar block (RLB) have been reported to be successful in providing analgesia after UVATS. However, which block technique provides superior analgesia after UVATS is still unclear. This randomized study was designed to compare the postoperative analgesic effects and adverse events associated with ultrasound-guided PVB and RLB after UVATS. Methods Sixty patients with lung cancer were randomized to undergo ultrasound-guided PVB (group P) or ultrasound-guided RLB (group R). In group P, 30 mL of 0.5% ropivacaine was injected at the T3 and T5 levels via ultrasound-guided PVB (15 mL at each level on the operative side). In group R, 30 mL of 0.5% ropivacaine was injected at the T3 and T5 levels via ultrasound-guided RLB (15 mL at each level on the operative side). The primary outcome was the numerical rating scale (NRS) score within 48 h after surgery. The secondary outcomes were total postoperative sufentanil consumption, time to first analgesic request and adverse events. Results At 3, 6, 12, 24, 36 and 48 h postoperatively, the NRS score at rest in group P was lower than that in group R (p < 0.05). At 3, 6, 12, 24 and 36 h postoperatively, the NRS score while coughing in group P was lower than that in group R (p < 0.05). The total postoperative sufentanil consumption in group P was significantly lower than that in group R (p < 0.001). Additionally, the time to first analgesic request was longer in group R than in group P (p < 0.0001). The incidence of nausea in group R was higher than that in group P (p < 0.05). Conclusions In patients with lung cancer undergoing UVATS, ultrasound-guided PVB with 0.5% ropivacaine provides better analgesia and results in less nausea than ultrasound-guided RLB. Compared with ultrasound-guided RLB, ultrasound-guided PVB seems to be a better technique for analgesia in UVATS. Trial registration The name of this study is the Effect And Mechanism Of Ultrasound-guided Multimodal Regional Nerve Block On Acute And Chronic Pain After Thoracic Surgery. This study was registered in the Chinese Clinical Trial Registry ( ChiCTR2100044060 ). The date of registration was March 9, 2021.